Biochemical alterations due to acute tannery effluent toxicity in Lemna minor L. - Lal, Nand (Journal of Phytology, 2009)
The effect of acute tannery effluent (TE) toxicity on some biochemical parameters in Lemna minor L. was studied using different TE concentrations i.e. 0 to 50.0% (v/V) in modified Hoagland's solution and exposure durations of 48 and 96 hours. The L. minor plants failed to survive at TE levels beyond 25.0%. The photosynthateÃ‚Â (starch) level increased above the control up to the 10.0% TE level, at higher concentrations it decreased to a level below the control and was comparatively higher at 96-hour exposure. Reducing sugar content at 48 hours did not show a clear trend but at 96 hours it followed a clear increasing trend up to 5.0% effluent level and subsequent concentrations showed decrease in reducing sugars. In the case of total soluble sugars at 48 hours, there was an increase up to 10.0% effluent after which it started decreasing till 25.0% level. However, at 96-hour exposure, total soluble sugars were maximum in control and showed a steady decreasing trend with increasing TE concentrations. The soluble proteins increased and were higher than the control at 48 hour exposure. However, 96 hour exposure to 20.0 and 25.0% effluent concentration revealed a marked decrease in soluble protein content. Total free amino acid content followed the trend observed with soluble protein up to 20.0% effluent level, after which their content decreased markedly. The acid phosphatase activity was higher at 48-hour exposure in comparison to 96 hour and showed an increasing trend with increasing effluent concentration at both the exposures. These biochemical constituents can be used as indices for measuring the phytotoxicity and understanding the mechanism and the level of tolerance to tannery effluent in L. minor.